2023
DOI: 10.3390/jcdd10050203
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Long-Term Heart Rate Variability between Subjects with and without Metabolic Syndrome: A Systematic Review and Meta-Analysis

Abstract: Background: Our aim was to determine the impact that metabolic syndrome (MS) produces in long-term heart rate variability (HRV), quantitatively synthesizing the results of published studies to characterize the cardiac autonomic dysfunction in MS. Methods: We searched electronic databases for original research works with long-term HRV recordings (24 h) that compared people with MS (MS+) versus healthy people as a control group (MS−). This systematic review and meta-analysis (MA) was performed according to PRISM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Indeed, it has been reported that reduced HRV is a marker of autonomic dysfunction, and it is already evident in patients with MS, even before the development of type-2 diabetes [ 62 ]. Thus, early detection of autonomic dysfunction in prediabetic patients using HRV would be as important as the screening for MS, since the progression of cardiovascular denervation is partly reversible or can be delayed in the early stages of the disease [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that reduced HRV is a marker of autonomic dysfunction, and it is already evident in patients with MS, even before the development of type-2 diabetes [ 62 ]. Thus, early detection of autonomic dysfunction in prediabetic patients using HRV would be as important as the screening for MS, since the progression of cardiovascular denervation is partly reversible or can be delayed in the early stages of the disease [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, heart rate variability (HRV), which analyses the fluctuations of the time intervals between heartbeats, has been shown to be an excellent tool for indirectly measuring the regulation of cardiac activity by ANS [28,29]. A recent systematic review and meta-analysis found that the main explanatory variables that differentiate patients with and without MetS are the standard deviation of the RR intervals (SDNN), the low-frequency (LF) and very low frequency (VLF) components, and total power, which were consistently decreased in patients with MetS [30], using long-term HRV analyses. However, data collected from clinical studies present a high degree of heterogeneity given the significant variability in age, sex and risk factors in the patient populations leading to each MetS definition.…”
Section: Introductionmentioning
confidence: 99%